Implementation of a multi-agent artificial intelligence system for financial trading decision-making process - Botunac, Ive (Oeconomica Jadertina, 2025)
The application of artificial intelligence in financial analysis leads to the development of advanced multi-agent systems that enable more effective analysis and decision-making than existing methods. This paper presents the development and implementation of a multi-agent artificial intelligence system for generating financial trading recommendations, integrating specialized agents for data collection, technical analysis, news processing, and portfolio management. The system combines quantitative analysis based on technical indicators with qualitative insights from financial news, utilizing natural language processing techniques such as prompt engineering and retrieval-augmented generation. The system's architecture enables autonomous operation of four specialized agents that contribute to generating trading recommendations. An evaluation conducted over six months in 2025 on five representative technology stocks reveals a significant improvement in risk management compared to the "buy and hold" reference strategy. Results demonstrate a significant reduction in volatility and maximum drawdown for most analysed stocks, particularly for highly volatile stocks such as Tesla, where the system maintains a maximum drawdown of 7.72% compared to 47.84% for the reference strategy. The system adapts trading recommendations to various market conditions and the specifics of each stock, thereby maintaining portfolio stability during periods of market instability. Financial news analysis using NLP enables the system to recognize whether news is positive or negative, its importance to the stock, and how it may affect its price. Despite identified limitations in adopting a more cautious approach during strong upward trends, the modularity of this architecture enables the continuous development and optimization of individual components. The research confirms the value of multi-agent approaches in integrating different data sources to improve the trading decision-making process.
Keywords: multi-agent systems; artificial intelligence; natural language processing; trading strategies; risk management